Ghosts of the current: environmental DNA assays to detect conservation priority areas for three critically endangered hammerhead sharks - Cardeñosa, Diego (Frontiers in Marine Science, 2025)
Small-bodied hammerhead sharks (Sphyrna corona, S. media, and S. vespertina) are among the most threatened and understudied elasmobranchs, yet little is known about their distribution or current status. Here, I developed and validated species-specific environmental DNA (eDNA) assays to enable rapid, non-invasive detection of these species in remote and turbid coastal environments. Assays targeting mitochondrial NADH2 and Control Region sequences were tested in vitro for specificity, sensitivity, and quantitative performance. All assays showed high specificity with no cross-amplification of non-target species, and strong linearity (R² > 0.99), with efficiencies between 0.848 and 0.908. In situ validation within Uramba/Bahía Málaga National Natural Park (Colombia) confirmed the presence of all three species. The scalloped bonnethead was the most frequently detected species, aligning with acoustic telemetry, fishery-independent surveys, and local ecological knowledge. Detections of S. media and S. vespertina were less frequent but consistent with known species ranges and habitat use. These findings underscore the park’s significance as a conservation hotspot for small hammerheads and demonstrate the utility of eDNA for monitoring rare sharks. This study provides a scalable molecular toolkit for detecting data-deficient elasmobranchs and supports evidence-based conservation planning in coastal regions threatened by overfishing and habitat degradation.